1998
DOI: 10.1007/bf03038478
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone-induced radioresistance occurring independent of human papilloma virus gene expression in cervical carcinoma cells

Abstract: In C4-1 and SW 756 cells, treatment with dexamethasone induces radioresistance, and changes in expression levels of HPV 18 genes E6 and E7 do not correlate with the changes in radiosensitivity. Dexamethasone-induced radioresistance has previously been observed in HeLa cells, another human cervical carcinoma cell line. This leads us to speculate that dexamethasone-induced radioresistance may be important in certain clinical situations, and that therefore, the phenomenon deserves further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
3

Year Published

1999
1999
2009
2009

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
0
10
0
3
Order By: Relevance
“…W hile investigating a potential role of oncogenic human papilloma virus (HPV) proteins with respect to radiosensitivity of cervical carcinoma cells, we recently became aware of the phenomenon of dexamethasone-induced radioresistance [22]. We found that radioresistance was induced in these cervical carcinoma cells by dexamethasone independent of the levels of papilloma virus gene expression (HPV type 18 genes E6 and E7), and that it was also independent of any related changes in rates of cell proliferation, such as suppression, no effect or promotion.…”
mentioning
confidence: 99%
“…W hile investigating a potential role of oncogenic human papilloma virus (HPV) proteins with respect to radiosensitivity of cervical carcinoma cells, we recently became aware of the phenomenon of dexamethasone-induced radioresistance [22]. We found that radioresistance was induced in these cervical carcinoma cells by dexamethasone independent of the levels of papilloma virus gene expression (HPV type 18 genes E6 and E7), and that it was also independent of any related changes in rates of cell proliferation, such as suppression, no effect or promotion.…”
mentioning
confidence: 99%
“…Insgesamt waren dies 181 Publikationen. Da Überlegungen zum Fehler zweiter Art international nur bei klinischen Untersuchungen üblich sind, wurden 33 physikalisch-technische Arbeiten [8-10, 22, 28, 38, 49, 52, 58, 61, 66, 79, 80, 82, 89, 92, 102, 106, 110, 111, 116, 119, 121, 141, 143, 146, 147, 149, 156, 159, 163, 169, 183], 19 In-vitro-Untersuchungen [11,13,21,35,55,56,78,97,100,103,112,120,126,135,142,148,161,179,182], sieben tierexperimentelle Untersuchungen [7,54,67,69,76,124,166] sowie zwei methodische [98,104] und eine demoskopische Arbeit [153] schlossen, in denen entweder keine eigenen Daten vorgestellt wurden [50,51,57,134,174] oder die keine quantitativen Ergebnisse enthielten; dies waren Übersichtsartikel [1,2,34,36,63,74,75,105,117,…”
Section: Qualitätsanalyse Der Zeitschrift "Strahlentherapie Und Onkolunclassified
“…Bei 26 Arbeiten (19%; 12%-27%) werden zum Teil Konfidenzintervalle gezeigt, jedoch nicht bei allen Ergebnissen und Grafiken [13, 17, 22, 31, 35, 56, 61, 70-72, 74, 78, 89, 101, 103, 108, 109, 112, 126, 131, 140, 160, 169, 170, 178, 179). Bei 15 Arbeiten (11%; 6%-18%) werden zwar Konfidenzintervalle gezeigt, es wird jedoch nicht immer eindeutig angegeben, um welches Konfidenzintervall es sich dabei handelt [43,45,48,49,60,61,76,86,93,96,135,138,154,155,157].…”
Section: Qualitätsanalyse Der Zeitschrift "Strahlentherapie Und Onkolunclassified
“…Hier ist die Angabe der Spannweite angezeigt. Bei sechs Publikationen (4%; 1%-10%) wird die Standardabweichung angegeben, obwohl das 95%-Konfidenzintervall oder wenigstens der Standardfehler sinnvoller gewesen wären [24,38,54,78,135,154].…”
Section: Qualitätsanalyse Der Zeitschrift "Strahlentherapie Und Onkolunclassified